FIR Filter Design using Raised Semi-ellipse Window Function - Henry N. Uzo; Helen U. Nonyelu; Joy N. Eneh; ThankGod I. Ozue; Edward C. Anoliefo; Vincent C. Chijindu; Ogbonna U. Oparaku (IAES Indonesian Section, 2022)
In this paper, a new two-parameter window function - Raised semi-ellipse (RSE) is proposed. The window is obtained from a fixed elliptical window known as Semi-ellipse window by raising the radius of the minor axis by the parameter (β), and applied for the design of finite impulse response (FIR) digital filters. The spectral parameters of the proposed window are determined first and compared with the Kaiser window – a 2-parameter adjustable window. Subsequently, in its application in filter design with an established design algorithm, the newly proposed adjustable window is compared to the Semi-ellipse window to examine its improvement and also the Kaiser window to compare its performance with a commonly used adjustable window. The filter simulation results show that the filters designed with the proposed window can provide more reduced ripples than the Kaiser window for prescribed spectral characteristics.